Immunometabolic Dysregulation at the Intersection of Obesity and COVID-19 - Khwatenge, Collins N.; Pate, Marquette; Miller, Laura C.; Sang, Yongming (Frontiers in Immunology, 2021)
Obesity prevails worldwide to an increasing effect. For example, up to 42% of American adults are considered obese. Obese individuals are prone to a variety of complications of metabolic disorders including diabetes mellitus, hypertension, cardiovascular disease, and chronic kidney disease. Recent meta-analyses of clinical studies in patient cohorts in the ongoing coronavirus-disease 2019 (COVID-19) pandemic indicate that the presence of obesity and relevant disorders is linked to a more severe prognosis of COVID-19. Given the significance of obesity in COVID-19 progression, we provide a review of host metabolic and immune responses in the immunometabolic dysregulation exaggerated by obesity and the viral infection that develops into a severe course of COVID-19. Moreover, sequela studies of individuals 6 months after having COVID-19 show a higher risk of metabolic comorbidities including obesity, diabetes, and kidney disease. These collectively implicate an inter-systemic dimension to understanding the association between obesity and COVID-19 and suggest an interdisciplinary intervention for relief of obesity-COVID-19 complications beyond the phase of acute infection.